2010
DOI: 10.1007/s10592-010-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of historical patterns of isolation by distance in coastal steelhead

Abstract: When natural populations exchange migrants at a rate proportional to their geographic distance, population genetics theory leads to the expectation of a pattern of isolation-by-distance (IBD), whereby geographic and genetic distance are correlated. However, the presence or absence of such patterns in modern populations may not fully reflect the historical relationships among those populations. Thus, historical samples, collected prior to modern human impacts, can often provide a critical baseline for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 46 publications
(45 reference statements)
7
43
2
Order By: Relevance
“…Isolation by distance is not an unusual pattern in freshwater systems (Pearse et al . ; Petrou et al . ), especially for species exhibiting low vagility as G. platei (Piedra et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation by distance is not an unusual pattern in freshwater systems (Pearse et al . ; Petrou et al . ), especially for species exhibiting low vagility as G. platei (Piedra et al .…”
Section: Discussionmentioning
confidence: 99%
“…History matters and processes taking place at disparate timescales need to be considered to avoid the over‐ or underestimation of the relative importance of the factors responsible for the generation and maintenance of genetic diversity (Pearse et al . ; He et al . ; Hansen et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pearse et al . () suggested that migratory routes have been interrupted in steelhead trout, Oncorhynchus mykiss , from comparisons of modern‐caught and historical specimens.…”
Section: Genetics and Genomicsmentioning
confidence: 99%
“…see Cambray, 2003). Native rainbow trout and other congeneric trout can suffer significant loss of genetic diversity and integrity due to hybridization with introduced hatchery populations (Pearse et al, 2010;Simmons et al, 2010;Finger et al, 2011). Such accounts are reported throughout the entire range of North American native trout.…”
Section: Worldwide Overview Of Negative Impacts Of Rainbow Trout On Nmentioning
confidence: 99%